Numerical analysis of Prosopis L. (Fabaceae) species from the coasts of Peru and Ecuador - Burghardt, Alicia D. (2010)
To the south of Ecuador and northern Peru is indicated the presence of 2 or 3 species of Prosopis: P. juliflora (SW) DC, P. pallida (Humb. et Bonpl. ex Willd.) Kunth and P. affinis Sprengel. In this paper we report the results of quantitative analysis of leaf characters of specimens of the genus Prosopis, collected along the coast from Arequipa (Peru) to Manta (Ecuador). The results point out three well defined groups. When we compare all the species and synonymous mentioned for the study zone with our results, conclude that are: P. pallida, P. limensis Bentham (both with a wide distribution) and P. chilensis (Molina) Stuntz emend Burkart restricted to the Camana river valley. It is pointed out the exclusion from the area of P. juliflora and P. affinis. We suggested that the several varieties mentioned for P. pallida should not be used for the moment.